2021
DOI: 10.1155/2021/5553173
|View full text |Cite
|
Sign up to set email alerts
|

Relevant SARS-CoV-2 Genome Variation through Six Months of Worldwide Monitoring

Abstract: Real-time genome monitoring of the SARS-CoV-2 pandemic outbreak is of utmost importance for designing diagnostic tools, guiding antiviral treatment and vaccination strategies. In this study, we present an accurate method for temporal and geographical comparison of mutational events based on GISAID database genome sequencing. Among 42523 SARS-CoV-2 genomes analyzed, we found 23202 variants compared to the reference genome. The Ti/Tv (transition/transversion) ratio was used to filter out possible false-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…Thus, RG-proteins will serve as very effective biomedicines that would be the most effective cheapest, nonphytotoxic, non-pollutant, conserve our biodiversity, and this vaccine might be the most effective against the delta variant of coronavirus, and scholars that give good scope for new development and future research in various fields of pathology-medical-pharmacology preventing fungal infections by increasing the post-COVID weakened lungs as well as the immune also. [15][16][17][18][19][20][35][36][37]39,67,[90][91] And in the near future ultra-high-diluted biomedicines; Gall30C, Gall 200C, and Gall 1000C pretreatment gall root (GR) may be used as mixing vaccines to provoke potent immune responses for the real-world efficacy and rare side effects. 92 And the Coronavirus 3′-5′ exoribonuclease (ExoN), substrate specificity and give insight into the molecular mechanisms of mismatch correction during coronavirus RNA synthesis, provide guidance for the rational design of improved anticoronavirus therapies, for the future mitigation strategies, and Covid appropriate and risk behavior at slums different areas also.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RG-proteins will serve as very effective biomedicines that would be the most effective cheapest, nonphytotoxic, non-pollutant, conserve our biodiversity, and this vaccine might be the most effective against the delta variant of coronavirus, and scholars that give good scope for new development and future research in various fields of pathology-medical-pharmacology preventing fungal infections by increasing the post-COVID weakened lungs as well as the immune also. [15][16][17][18][19][20][35][36][37]39,67,[90][91] And in the near future ultra-high-diluted biomedicines; Gall30C, Gall 200C, and Gall 1000C pretreatment gall root (GR) may be used as mixing vaccines to provoke potent immune responses for the real-world efficacy and rare side effects. 92 And the Coronavirus 3′-5′ exoribonuclease (ExoN), substrate specificity and give insight into the molecular mechanisms of mismatch correction during coronavirus RNA synthesis, provide guidance for the rational design of improved anticoronavirus therapies, for the future mitigation strategies, and Covid appropriate and risk behavior at slums different areas also.…”
Section: Discussionmentioning
confidence: 99%
“…Open Sci. 11: 231369 the literature a consensus that in the SARS-CoV-2 genome mutations are strongly biased towards C → T transitions (see [23,25,26]). Another feature which is apparent from figure 1a is that the data points are organized in clusters.…”
Section: Relative Entropy Analysismentioning
confidence: 99%
“…And it is also noted that the ultra-high-diluted biomedicines Gall 200C will be the most potential preventive biomedicine vaccines due to its very close related genetic structure, emerging body of molecular evidences suggested a similar path to SARS and MERS viruses, and once they entered inside body, they overtake the cell's machinery, replicate, multiply and infect the adjoining cells, and all the viruses have a tell-tale signature on the surface known as antigens, identifying these antigens is what activate the immune system by producing the antibodies. And researchers have shown that a wide range of immune cells that react to SARS-CoV-2 and helps in recovery could be helpful in the development of potential vaccines against 'Genome Variation' [1,2,95,96].…”
Section: On Genetic Pretreatment Effects On Orgs Pr-proteins-genesmentioning
confidence: 99%
“…The different ultra-high-diluted biomedicines including Gall 200C, and Nematode 200C-pretreated okra root galls (ORG) protein could be induced the production of new defense-related PR-genes in the test plants and might be confirmed, and in near future, synthetic production of the particular RG-proteins-genes might be the most potential costeffective emergency personalized-biomedicine vaccines against coronavirus 2 like pandemic viral diseases by increasing immunity, and helping policy initiative clinical research in all areas in the field of advanced medical, pharmaceutical, science, technology, communication, agriculture, environment, health, socio-economy, agronomy, plant breeding, horticulture, aquatic sciences, and different issues by preventing plant diseases and COVID-19 like variants also. Thus, RG-proteins will serve as the most effective biomedicines vaccine that might be the potential cheapest, non-phytotoxic, non-pollutant, conserve our biodiversity, and this vaccine might be the most effective against the delta variant of coronavirus, and scholars that give good scope for new development and future research in various fields of pathology-medical-pharmacology preventing fungal and brain infections by increasing the post-COVID weakened lungs as well as the immune also [1,2,[15][16][17][18][19][20][21][22]25,[40][41][42][43][44]71,[90][91][92][93][94][95][96][97]. And in the near future ultra-high-diluted biomedicines; Gall 200C, and Nematode 200C pretreatment gall GR or NF may be used as mixing vaccines to provoke potent immune responses for the real-world efficacy and rare side effects [98].…”
Section: Development Of Future Drug or Vaccines Ideamentioning
confidence: 99%